Closing address. Rural development in the mediterranean region in a changing trade and co-operation environment - Plaskovitis I. (The GATT and Mediterranean agricultural trade, 1997)
This closing address to the seminar of 'the GATT and Mediterranean agriculture trade' focuses first on Greece agriculture which characteristics are quite typical of Mediterranean agriculture. The author expresses hesitation about the new Common Agricultural policy especially for the small Mediterranean farmer.
Séminaire sur 'Le GATT et les Echanges Agricoles Méditerranéens', 1995/12/03-05, Chania (Greece)